2011
DOI: 10.1016/j.scitotenv.2011.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and meteorological analysis of two Australian dust storms in April 2009

Abstract: Dust is an important source of bioaerosols including bacteria. In this study, the microbiology and meteorology of specific dust storms in Australia were investigated. The samples were collected from two dust events in April 2009 that were characterised by intense cold fronts that entrained dust from the highly erodible and drought-stricken Mallee and Riverina regions of Victoria and central NSW. In the first storm, the dust travelled eastward over Canberra and Sydney, and in the second storm, the dust travelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Charles Darwin and his friend Christian Ehrenberg showed that airborne dust contains organic material (Darwin, 1846). Microbes that hitchhike on desert dust are now known to spread across the globe (Griffin et al, 2003a, b;Kellog et al, 2004;Prospero et al, 2005;Kellogg and Griffin, 2006;Weir-Brush et al, 2004;Lim et al, 2011). Gorbushina et al (2007) used geochemical methods to show that the Darwin/ Ehrenberg dust probably originated from the Sahara.…”
Section: Introductionmentioning
confidence: 99%
“…Charles Darwin and his friend Christian Ehrenberg showed that airborne dust contains organic material (Darwin, 1846). Microbes that hitchhike on desert dust are now known to spread across the globe (Griffin et al, 2003a, b;Kellog et al, 2004;Prospero et al, 2005;Kellogg and Griffin, 2006;Weir-Brush et al, 2004;Lim et al, 2011). Gorbushina et al (2007) used geochemical methods to show that the Darwin/ Ehrenberg dust probably originated from the Sahara.…”
Section: Introductionmentioning
confidence: 99%
“…Culturable UV-tolerant bacterial strains were also isolated in the previous studies carried on near grounds in the arrival areas of Asian, African and Australian dust Hua et al, 2007;Lim et al, 2011). However, these studies could not omit the background or bacteria from local sources, meaning that previous results could contain not only the compositions of bacteria transported in dust but also some few bacterial compositions aerosolized from near sampling sites.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Moreover, the deposition of dust on irrigation canals and rivers affects the water quality of streams, lakes and oceans. [13][14][15][16][17] A study by Lim et al [18] highlighted the contribution of dust events to the distribution of microbes in the environment from two dust storms in Australia.…”
Section: Introductionmentioning
confidence: 99%